PELATIHAN PEMBUATAN PETA IRIGASI SEBAGAI UPAYA SISTEM PENINGKATAN PERTANIAN DAN KETAHANAN PANGAN - Nurul Asid; Alwan Gangsar Brilian Putra; Danayanti Azmi Dewi Nusantara; Mas Suryanto HS; Nurhayati Aritonang (Universitas Kadiri, 2026)
This Community Service Program aims to strengthen rural community empowerment through technical assistance in optimizing irrigation system management, thereby contributing to the achievement of the national food security agenda. The program is implemented in partnership with the Tanggumong Village Government, which possesses strong agricultural potential but faces limitations in infrastructure and technical capacity. The intervention focuses on training village officials in the development of an irrigation mapping system to enhance their competencies in identifying, documenting, and analyzing the spatial distribution and condition of irrigation channels. These enhanced skills are expected to enable the village government to conduct evidence-based planning and sustainable development of irrigation infrastructure while improving information accessibility for both local communities and policymakers. The PKM is scheduled for August 11–15, 2025, and will be conducted onsite at the Tanggumong Village Hall through three stages: coordination, training, and evaluation. Moreover, this initiative fosters stronger institutional collaboration between the university and local partners, promoting the integration of community service, student fieldwork (KKN), and lecturer–student collaborative research.